2015
DOI: 10.4236/psych.2015.611134
|View full text |Cite
|
Sign up to set email alerts
|

Between Scylla and Charybdis: A Literature Review of Sexual Abuse Allegations in Divorce Proceedings

Abstract: In this study international literature is reviewed on allegations of child sexual abuse (CSA) during divorce proceedings. It aims to build upon the existing knowledge on this topic by combining empirical findings from various disciplines. We attempted to answer four research questions that focus on 1) the prevalence of CSA allegations in divorce procedures; 2) the response of family court judges; 3) the ratio of founded vs. unfounded allegations of CSA under these circumstances; and 4) the possible consequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Second, our effect sizes in this study were small, and participants often did not endorse any intervention as appropriate, regardless of the gender of the parent. Third, our results both align (Meier and Dickson 2017;Priolo-Filho et al 2019) and contrast with previous research suggesting a bias against males in family court cases (Kelly and Johnston 2008;O'Donohue et al 2016a, b;Smit et al 2015;Stathopoulos 2013). Given this split in the research and potential differences resulting from beliefs as to rates of perpetration of sexual abuse by males and females, further studies must be conducted to replicate and elucidate the mechanism underlying these findings.…”
Section: Differential Effect Of Gender On Outcomes In Parental Alienasupporting
confidence: 61%
See 1 more Smart Citation
“…Second, our effect sizes in this study were small, and participants often did not endorse any intervention as appropriate, regardless of the gender of the parent. Third, our results both align (Meier and Dickson 2017;Priolo-Filho et al 2019) and contrast with previous research suggesting a bias against males in family court cases (Kelly and Johnston 2008;O'Donohue et al 2016a, b;Smit et al 2015;Stathopoulos 2013). Given this split in the research and potential differences resulting from beliefs as to rates of perpetration of sexual abuse by males and females, further studies must be conducted to replicate and elucidate the mechanism underlying these findings.…”
Section: Differential Effect Of Gender On Outcomes In Parental Alienasupporting
confidence: 61%
“…In contrast, there are reasons to believe that family court professionals may actually be more likely to find alienation when a male parent claims child sexual abuse than when a female is the alleged perpetrator. Family court officials might not believe men as frequently due to males' increased association with aggression and violence, including abuse, compared with females (O'Donohue et al 2016a, b;Smit et al 2015;Stathopoulos 2013). Males are also more likely to perpetrate child sexual abuse than females (Finkelhor 1984).…”
Section: Gender Of the Alienating Parent And Child Maltreatment Allegmentioning
confidence: 99%
“…So while these figures show that making false allegations is not commonplace, the rates are higher in cases of parental separation than in other contexts, particularly for the non-custodial parent. Specifically, in their reviews of research on child sexual abuse during divorce, Penfold [ 3 ] states that 8% to 16.5% of reports are false and Smit, Antokolskaia and Bijleveld [ 4 ], found that one out seven cases are unfounded. In a different but related domain, the General Council of the Judiciary in Spain [ 5 ] found very low numbers (0.4%) of false reports in intimate partner violence cases.…”
Section: Introductionmentioning
confidence: 99%
“…It was originally argued that women are the primary perpetrators of alienation (Gardner 1992a, b), and this gender bias has led to family court professionals being more likely to identify a case as containing PA when the alleged alienator is the mother rather than the father (Priolo-Filho et al 2019). However, when child sexual abuse is claimed in a custody case, fathers alleging that the mother has committed child sexual abuse are less likely to be believed than when the mother makes the same claim against the father (O'Donohue et al 2016;Smit et al 2015;Stathopoulos 2013). In the Goldfarb et al study, professionals from Brazil (compared with those from the USA) were more likely to find PA in cases with parental hostility and generally more likely to recommend interventions, with the exception of cases including child sexual abuse, for which US professionals were more likely than Brazilian professionals to recommend an intervention.…”
Section: Department Of Health and Human Services 2017)mentioning
confidence: 99%